Characterisation of the professional identity of teachers of vocational and technical training in Senegal: an exploratory study - BABA DIÈYE DIAGNE; HÉLÈNE CHENEVAL-ARMAND (Metaichmio Publications, 2023)
This paper presents an approach to characterising the professional identity of technical vocational teachers based on psychosociological indicators. The indicators are based on the scientific literature and refer to the representation of colleagues and the profession to oneself and the representation of oneself as a person. A questionnaire survey was submitted to two groups of teachers with several years of service. The first group was made up of teachers with a professional degree. The second group consisted of contract teachers who teach without a professional diploma. This study shows the existence of several identity profiles of technical vocational training (TVET) teachers in Senegal.